Implementation status of community adaptation plans: a case study from Parbat District, Nepal - Acharya, Reeti; Paudel, Ganesh (International Journal of Environment, 2016)
This study was carried out in three community forests of the Parbat District, Nepal with the objective of assessing the implementation status of Community Adaptation Plans (CAPs). Three focus group discussions, observations and several informal discussions were made with the local people. Physical and financial progresses of the CAPs were assessed. Altogether 26 climate change adaptation activities were proposed for the fiscal year 2071/72 among them 46% activities were implemented completely, 19% activities were started but not implemented and 35% activities were not implemented. The physical and financial progresses of the CAPs were 41.79% and 27.47 % respectively. For ensuring the effective implementation of CAPs mainstreaming them into local level development plan is recommended. Analysis of the effectiveness of the implemented CAPs in reducing vulnerability is recommended for future researchers. International Journal of Environment Vol.5(3) 2016, pp.119-126